PENERAPAN INTERNET OF THINGS UNTUK KEANGGOTAAN PERPUSTAKAAN UNIVERSITAS WIRALODRA BERBASIS RFID - Sodikin, Luthfia; Pauzan, Muh; Yanti, Indri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
This research aims to address the challenges in library service management at Wiralodra University by implementing an Internet of Things (IoT)-based book borrowing system. The Mixed-Methods approach is employed, combining qualitative and quantitative data. Utilizing NodeMCU Esp8266, RFID RC522, LED, Buzzer, and LCD I2C for hardware, and PHP programming language with a MySQL database for software, the system enables self-registration of new members, book borrowing, and returns. Test results show an average card reading time of 8 seconds for unregistered cards and 7 seconds for registered ones. Implementation of this system enhances service efficiency, reduces time wastage, and provides a more convenient borrowing experience for students. This research offers an effective solution to enhance IoT-based library management, improving access to knowledge for Wiralodra University students.